2021
DOI: 10.1177/1757975921992957
|View full text |Cite
|
Sign up to set email alerts
|

Individual, social and national coping resources and their relationships with mental health and anxiety: A comparative study in Israel, Italy, Spain, and the Netherlands during the Coronavirus pandemic

Abstract: Employing the salutogenic model, we asked how individuals in different countries cope with the COVID-19 crisis and stay healthy. We were interested in exploring the individual (i.e. sense of coherence) as well as the social and national resources (i.e. social support, sense of national coherence, and trust in governmental institutions) that could explain levels of mental health and anxiety during the outbreak of the pandemic. Data collection was conducted via convenience sampling on online platforms, during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 16 publications
5
23
0
Order By: Relevance
“…According to PMT, difficulty in sustaining biocentric connections of individuals to themselves, others, and nature during the pandemic may play a crucial role in the development of anxiety, depression, stress, and post-traumatic stress, loneliness, social isolation, and stigma. Similar observations were made by the study of Super et al (2020) where mental health condition was predicted by the sense of individual and national coherence and the presence of social support.…”
Section: Introductionsupporting
confidence: 81%
“…According to PMT, difficulty in sustaining biocentric connections of individuals to themselves, others, and nature during the pandemic may play a crucial role in the development of anxiety, depression, stress, and post-traumatic stress, loneliness, social isolation, and stigma. Similar observations were made by the study of Super et al (2020) where mental health condition was predicted by the sense of individual and national coherence and the presence of social support.…”
Section: Introductionsupporting
confidence: 81%
“…The current study explored the mediating role of two GRRs on the relationships between SOC and mental health: at the micro level – one's perceived support from one's family, and at the macro level – trust in leaders, social, and political institutions that are responsible for managing the pandemic. Those GRRs have been found in previous studies as relevant to coping with the COVID-19 pandemic in various countries ( Mana & Sagy, 2020 ; Mana et al., 2021 ).…”
Section: Introductionsupporting
confidence: 67%
“…A few recent studies have already reported the main contribution of SOC to coping with the COVID-19 pandemic. SOC was correlated with emotional distress among different cultural groups ( Barni et al., 2020 , Braun-Lewensohn et al., 2021 ) SOC was reported as a better predictor of mental health than demographic variables (e.g., gender, age, and education); risk factors (e.g., health and economic level of risk); or other coping resources (e.g., trust, family support) in different social contexts during the acute stage of the pandemic ( Généreux & Roy, 2020 ; Hardy et al., 2021 ; Mana & Sagy, 2020 ; Mana et al., in press ).…”
Section: Introductionmentioning
confidence: 99%
“…Survey development is based on the salutogenic model and explored coping resources: SOC ( SOC‐13 , Antonovsky, 1987), SONC (Mana et al, 2019), level of trust in relevant institutions (i.e., media, legal courts, the president, Centers for Disease Control, police, the government, health‐care workers, and hospitals) and one's perceptions of the social support one receives in the time of crisis from one's social circles (family, community, friends, social media, work colleagues), as predictors of levels of mental health (MHC‐SF, Lamers et al, 2011) and general anxiety (GAD‐7, Spitzer et al, 2006) (Mana & Sagy, 2020). Surveys of this type are used to explore SOC and SONC in a large dataset that can be quantitatively measured and compared across nation state allegiances and borders (Mana et al, 2021). For the current study we used multiple regression analysis and Pearson correlation analyses to explore the relationships between the coping resources and mental health and anxiety in a sample of 249 women who declare that they voted for a left‐leaning party in the last election.…”
Section: Methods and Analysismentioning
confidence: 99%